2021
DOI: 10.4236/ojas.2021.111006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth Performance, Carcass Characteristics and Meat Quality of Local Horro and Exotic Cockerels of Tropical Origin Fed Growers Diet

Abstract: Growth performance, carcass characteristics and meat quality of male chickens were evaluated using eight-week-old 360 cockerels from three exotic (Koekoek, Kuroiler and Sasso-R) and one Ethiopian indigenous (Horro) genotypes. Cockerels in each breed (90) were randomly allocated into three replications of 30 birds each and housed in deep litter pens for the experiment that lasted for 8 to 16 weeks. The experiment was arranged in a Completely Randomized Design. Seven birds per breed were slaughtered at the end t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Likewise, Sasso had significant (P < 0.05) higher carcass weight and Dressing percentage (DP %) than Kuroiler which implies existence of genetic differences between the two breeds in growth rate and muscle deposition. This observation agrees with the reports of Mueller et al [3], Ibrahim et al [8] and Biazen et al [7] who also revealed the existence of breed/genotype differences in the slaughter weight of chickens. As expected, birds with higher growth potentials (i.e., higher BWs) will present a higher meat production capacity (carcass yield).…”
Section: Effect Of Breed On Carcass Characteristicssupporting
confidence: 93%
See 2 more Smart Citations
“…Likewise, Sasso had significant (P < 0.05) higher carcass weight and Dressing percentage (DP %) than Kuroiler which implies existence of genetic differences between the two breeds in growth rate and muscle deposition. This observation agrees with the reports of Mueller et al [3], Ibrahim et al [8] and Biazen et al [7] who also revealed the existence of breed/genotype differences in the slaughter weight of chickens. As expected, birds with higher growth potentials (i.e., higher BWs) will present a higher meat production capacity (carcass yield).…”
Section: Effect Of Breed On Carcass Characteristicssupporting
confidence: 93%
“…2kg for fast-growing chickens kept for less than 8 weeks. This supports the suggestion by Biazen et al [7] that despite the longer growing period required for dual-purpose chicken breeds than the fast-growing broiler, males of the two breeds can still be utilized as alternative meat-type chicken in places where specialized broilers are not accessible or where the local types are considered to be uneconomical given their slow growth and lower body weight at slaughter. The dressing percentage (DP %) was higher for Sasso (70.63%) than Kuroiler (68.54%) which is likely the result of higher bodyweight of Sasso chickens.…”
Section: Effect Of Breed On Carcass Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…The overall mean of the carcass weight for Kuroiler chickens observed in the present study is higher than 1400.6g for Koekoek chickens reported by Ibrahim et al Breast meat yield is the carcass component with the highest economic value followed by legs (thigh + drumstick). These parts are considered the most valuable parts in broiler and dual-purpose male chickens kept for meat production, while the back, wing and neck are less valuable parts (Biazen et al 2021). The higher breast weight relative to other carcass parts might be related effect of selection for meat production where more attention is placed on the breast proportion (Marapana 2016).…”
Section: Declarationsmentioning
confidence: 99%
“…The BW of each kid was weighed on the 1st day and 74th day of the trial period before morning feeding. The body weight change (BWC), average daily gain (ADG), and feed conversion ratio (FCR) were calculated until the end of the experiment, according to Biazen et al [21]. The formulas for calculation were as follows: BWC (kg) = final weight (kg) − initial weight (kg); ADG (g/d) = BWC (kg)/74 × 1000; FCR = DMI (g/d)/ADG (g/d).…”
Section: Growth Performancementioning
confidence: 99%